2013
DOI: 10.1093/cid/cit146
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis Treatment Response Among HIV-Discordant Couples in Zambia and Rwanda

Abstract: In 2 HIV-serodiscordant couple cohorts in Africa, incident syphilis had a very good likelihood of response to penicillin therapy, irrespective of HIV infection. This supports current Centers for Disease Control and Prevention treatment guidelines. A high proportion of prevalent RPR-positive infections remain serofast despite treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 35 publications
5
36
0
2
Order By: Relevance
“…72 Similarly, penicillin therapy appeared to be effective at treating incident cases of syphilis in HIV-serodiscordant couples, irrespective of HIV status. 74 Although treatment of HSV-2 with nucleoside analogs such as acyclovir and valacyclovir has been shown to reduce the occurrence of genital ulcers among PLHIV, 73 it is unclear if these medications impact ulcer healing. 77,78 Acyclovir treatment, however, may reduce the risk of HIV disease progression (defined as CD4 <200 cells/mm 3 or WHO clinical stage 4) by as much as 16%.…”
Section: Resultsmentioning
confidence: 99%
“…72 Similarly, penicillin therapy appeared to be effective at treating incident cases of syphilis in HIV-serodiscordant couples, irrespective of HIV status. 74 Although treatment of HSV-2 with nucleoside analogs such as acyclovir and valacyclovir has been shown to reduce the occurrence of genital ulcers among PLHIV, 73 it is unclear if these medications impact ulcer healing. 77,78 Acyclovir treatment, however, may reduce the risk of HIV disease progression (defined as CD4 <200 cells/mm 3 or WHO clinical stage 4) by as much as 16%.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies compared treatment responses in HIVinfected persons and HIV-uninfected persons with syphilis. The data from 2 observational cohorts in Africa suggest that HIV-infected and HIV-uninfected persons responded similarly to therapy [21]. A retrospective study by Farhi et al that compared HIV-infected and -uninfected persons with early syphilis found similar responses to therapy in both groups [26].…”
Section: Discussionmentioning
confidence: 99%
“…Composite variables for genital ulceration were created from time-varying measures of chronic/recurrent or acute genital or perianal ulcers (whether diagnosed/treated at the research clinic or reported by the client); ulceration upon physical examination (including erosion or friability of the cervix or vagina in women); or newly positive rapid plasma reagin serology for syphilis [18]. Composite variables for genital inflammation were created from time-varying measures of genital inflammation, genital discharge and trichomoniasis, gonorrhea, chlamydia, candida or bacterial vaginosis [19].…”
Section: Methodsmentioning
confidence: 99%